PEMAHAMAN MASYARAKAT TENTANG HUKUM NIKAH KARENA TELAH MELAKUKAN PERZINAHAN - Naziroh, Ima; Hermawan, Iwan; Waluyo, Kasja Eki (Universitas Islam Madura, 2024)
Pregnancy out of wedlock is an act that is forbidden by religion, because religion teaches humans to be virtuous, however, we still often encounter this practice in society. Thus, researchers are interested in exploring and understanding this phenomenon. The library research method, also known as a literature review, is an approach used to collect, review, and synthesize existing knowledge in the literature that is relevant to the research topic. In the context of society's understanding of the law on marriage for adultery. The results of the research show that in Islamic law adultery is an act that is strictly forbidden in Al-Isra verse 32 and the perpetrator of adultery must be punished in the form of 100 lashes, exiled for 1 year and sentenced to stoning. Meanwhile, according to Law no. 1 of 1974 concerning Marriage only regulates the status of children resulting from adulterous relationships. The legal consequences of marrying a pregnant woman due to adultery are according to Islamic law. The child born has no lineage to his father, even though the father who married the mother is the one who committed adultery, the lineage of the child resulting from adultery is only related to the mother. Then, children resulting from adultery do not have the right to inherit and there is no right to support, if a woman is born, her father cannot be guardian of her when she marries. The implications of this research include 1) increasing legal awareness for the community, 2) changing social perceptions of community legal phenomena, 3) improving the legal system, 4) improving social services, 5) advocating for legal awareness and 6) increasing the role of community education.